Crystal defects responsible for mechanical behaviors of a WC–Co composite at room and high temperatures – a simulation study. Issue 2 (13th March 2019) - Fang, Jing; Liu, Xuemei; Lu, Hao; Liu, Xingwei; Song, Xiaoyan
Abstract : Evolutions of microstructure and crystal defects in the nanocrystalline WC–Co composite during room‐ and high‐temperature deformations were studied using molecular dynamics simulations. Abstract : The microstructure evolution and changes in the structures of crystal defects of the nanocrystalline WC–Co composite in the process of uniaxial compression were studied by simulations at both room and high temperatures. The deformation processes were demonstrated as a function of stress and temperature for the stages prior to and after yielding of the composite. The Peierls stresses were evaluated for Co and WC dislocations with increasing temperature. The deformation mechanisms for each stage of the stress–strain curve were disclosed, in which the effect of temperature was clarified. It was found that with the increase of stress, from elastic deformation to plastic deformation then to yielding of the composite, the dominant mechanisms are grain boundary migration, formation and motion of dislocations in Co, concurrent motion and reaction of dislocations in Co and WC, and then rotation of WC grains in combination with motion of Co and WC dislocations. At the yielding stage, sliding of WC grain boundaries plays an increasingly important role in the contribution to plastic deformation at high temperatures. With strain the proportion of mobile dislocations decreases, and dislocations pile up at triple junctions of WC grains, WC/WC grain boundaries and WC/Co phase boundaries in priority order, leading to the nucleation and propagation of microcracks in these regions.